Pain detection by clinical questionnaire in patients referred for temporomandibular disorders in a Chilean hospital. - Tomás Maturana; Patricio Ruiz; Cristian Rosas; Pedro Aravena (Universidad de Concepción., 2015)
Aim: To determine pain frequency by means of a clinical screening questionnaire in patients with temporomandibular disorders (TMD) referred to the general Hospital of Valdivia (HBV) between September and December 2014. Material and method: A descriptive study, which included patients referred to the TMD Unit of the dental service at HBV between September and December 2014, was carried out. A clinical screening questionnaire was applied by an examiner in order to detect painful Temporomandibular Joint Disorders. The variables age, sex, wait time, and presence of related TMD pain were measured. Results: 101 patients were surveyed; 88.17% (84 patients) were women. Average age was 33.5 (11-70) years; 66% of patients had mandibular pain or stiffness upon awakening; 80% informed pain related to painful TMD. Conclusion: Most surveyed patients were women. Pain was highly frequent in the surveyed population; its main location was in temporal areas.